CAN GOOD GUYS FINISH FIRST? : A follow-up study on employee satisfaction and stock prices - Hyrkäs, Maiju Pauliina (My University, 2020)
The rapid growth of both investor and academic interest towards socially responsible investing has produced a large number of scientific papers studying the relationship between corporate social responsibility and returns. In 2011 Edmans published a paper that reported abnormal superior returns for a portfolio constructed of the annual “100 Best Places to Work For in America” list. The study concluded that the superior returns were caused by the market’s inability to incorporate employee satisfaction into stock prices. The modern financial theory and empirical evidence have shown nonetheless that when the market learns to adjust their valuations of underpriced assets, and superior returns do not persist in the long run. The thesis employs the Carhart four-factor model on a Best Companies portfolio to investigate whether the returns shown by Edmans still occur on a more recent period. The results of the analysis show negative returns for the Best Companies portfolio, and after adjusting for industries the results stay negative yet slightly less so. The results confirm the initial expectations that market learning has taken place, most likely due to the increasing level visibility of the 100 Best Companies list and public’s interest towards socially responsible investing.
Keywords: human capital; social responsibility; stock prices; corporate responsibility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance